The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1074/jbc.274.33.23577
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Regulatory Element Binding Protein-1 Expression Is Suppressed by Dietary Polyunsaturated Fatty Acids

Abstract: Polyunsaturated fatty acids (PUFA) coordinately suppress the transcription of a wide array of hepatic lipogenic genes including fatty acid synthase (FAS) and acetyl-CoA carboxylase. Interestingly, the over-expression of sterol regulatory element binding protein-1 (SREBP-1) induces the expression of all of the enzymes suppressed by PUFA. This observation led us to hypothesize that PUFA coordinately inhibit lipogenic gene transcription by suppressing the expression of SREBP-1. Our initial studies revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
343
4
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(380 citation statements)
references
References 45 publications
(76 reference statements)
26
343
4
7
Order By: Relevance
“…This contradicts previous studies demonstrating that polyunsaturated fatty acids (PUFA) inhibited lipogenic gene transcription by suppressing SREBP-1c expression (Kim et al, 1999;Xu et al, 1999). Xu et al (1999) also indicated that the SREBP-1 mRNA content of cells was reduced by 20:4n-6 fatty acids in a dose-dependent manner, whereas 18:1n-9 had no effect. However, the exact amount of 20:4n-6 fatty acids was not determined by Yang et al (2010).…”
Section: Discussioncontrasting
confidence: 84%
“…This contradicts previous studies demonstrating that polyunsaturated fatty acids (PUFA) inhibited lipogenic gene transcription by suppressing SREBP-1c expression (Kim et al, 1999;Xu et al, 1999). Xu et al (1999) also indicated that the SREBP-1 mRNA content of cells was reduced by 20:4n-6 fatty acids in a dose-dependent manner, whereas 18:1n-9 had no effect. However, the exact amount of 20:4n-6 fatty acids was not determined by Yang et al (2010).…”
Section: Discussioncontrasting
confidence: 84%
“…This idea is supported by the fact that the overexpression of mature SREBP1 overrides the PUFA suppression of lipogenic gene expression (Yahagi et al 1999), and by a study using animal models which showed that the decrease of the mature form of SREBP1 after administration of fish oil rich in n-3 PUFA results in decreased expression of lipogenic enzymes including SCD1 (Xu et al 1999). Moreover, n-3 PUFA has been related to the control of the proteolytic processing of SREBP precursors (Pegorier et al 2004) and its modulator effect in decreasing the lipogenesis process through inhibition of SREBP1 in adipocytes (Madsen et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…EPA and DHA have been shown to be ligands for nuclear receptors such as PPAR-alpha (23,24,25) and sterol regulatory element binding proteins (23,26), which modulate the expression of key genes in these metabolic processes. Now DPA may also be involved in these processes.…”
Section: Discussionmentioning
confidence: 99%